Preparing Future Talent: Career Adaptability And Employability Among Management Undergraduates - Muhaidir Ikram; Josafat Gracia Ginting; Ahmad Rais Habib (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to examine the effect of career adaptability on employability and to analyze differences in both variables based on cohort year and academic concentration among Management undergraduates at Universitas Negeri Makassar. This research employed a quantitative explanatory-comparative survey design. The population consisted of 851 active Management students from the 2021–2023 cohorts, while the sample comprised 130 students selected through proportionate stratified sampling. Data were collected using a structured questionnaire with a 4-point Likert scale. Career adaptability was measured using an adapted Career Adapt-Abilities Scale covering concern, control, curiosity, and confidence, while employability was measured using an adapted Employability Appraisal Scale covering work-readiness supportive behaviors, work-capital readiness, job-seeking behavior, self-control, and self-learning. Data were analyzed using descriptive statistics, validity and reliability tests, simple linear regression, and one-way ANOVA. The results show that all dimensions of career adaptability and employability were in the high category. Career adaptability had a positive and significant effect on employability, with an R Square value of 0.460, indicating that career adaptability explained 46.0% of the variance in employability. However, career adaptability and employability did not differ significantly based on cohort year or academic concentration. The study concludes that career adaptability is a key predictor of employability and should be strengthened through career coaching, experiential learning, internships, and industry-linked programs.